Efek FOMO dalam Kampanye Flash Sale E-Commerce terhadap Perilaku Impulsif Konsumen: Studi Kuantitatif pada Generasi Muda Indonesia - Fadali Rahman; Umi Wahyuni; Diana Afriliana; Nurmalina Anastasya; Nur Laili (PT. Hasba Edukasi Mandiri, 2025)
This study provides an in-depth examination of the influence of Fear of Missing Out (FOMO) on consumers’ impulsive buying behavior during e-commerce flash sale campaigns, focusing on Indonesia’s digitally active youth. Employing a quantitative approach, data were collected from 100 respondents aged 18–35 via a Likert-scale questionnaire and analyzed using simple linear regression. The results reveal a positive and significant effect of FOMO on impulsive behavior (b = 0.678, Sig. = 0.000, R² = 0.462), reinforcing the Stimulus–Organism–Response (SOR) model, with FOMO acting as a psychological mediator between promotional strategies and consumer responses. These findings not only deepen theoretical understanding of psychological dynamics in digital marketing but also offer practical implications for e-commerce practitioners in designing ethical, effective, and sustainable campaigns. The study highlights the need for balancing promotional urgency with consumer literacy and opens avenues for further exploration into the interplay between digital social pressure and spontaneous purchasing decisions.